ACCESS METHOD TO THE LEARNING OF BASIC TECHNICAL-TACTICAL HANDBALL ELEMENTS - Dobrislav Vujović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
The analysis of the handball development tendencies demands more and more sophisticated work forms and methods which provide possibility of the quick and good quality implementation of the setup goals and tasks in the work with children. In that case it becomes very important to create the best methods and instruments by which, with the systematic work, the acquired technical/tactical skils and motoric capacities will be adopted and automatized. Process of acquiring of technical/tactical skills and motoric capacities represents main goal in the overall training process of young handball players. It is also a part of the transformation process and an important prerequisite of the specifi c handball competition activity. During the systematic work e.g. training process, from the beginner to the top handball player, this learning process is very unique and in interwoven. It is going on by following general training rules with the purpose of creating supreme sport result